Analysis of Cracking Reasons of the Second Quench Heat Exchanger Cylinder - ZHANG Sheng-nan, ZHAO Wen-bin, TONG Ai-qun, LU Zhong-hai (Cailiao Baohu, 2021)
The second quench heat exchanger is the core equipment of the ethylene plant of a petrochemical company.There was a sudden leak in the heat exchanger in May 2018, causing the equipment to stop.Through the inspection it was found that the leakage mainly occurred in the first barrel section of the heat exchanger shell near the upper tube plate.There was a penetrating crack in the failure position of the cylinder, and the crack was completely cracked along the direction of thickness.For this, the original manufacturing data of the equipment were reviewed, and the stress analysis, macroscopic examination and sampling analysis of the cracking phenomenon of the cylinder of the heat exchanger were carried out.Results showed that alkali stress corrosion was the fundamental cause of heat exchanger cylinder failure and cracking, meanwhile the corresponding preventive measures were put forward.